Pengembangan e-modul dengan flip pdf corporation pada pembelajaran tahfizh al-Qur’an - Admalinda Admalinda; Fadriati Fadriati; Lita Sari Mukhlis; Ravino Yuranda (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to determine the validity and practicality of E-Module Development with Flip Pdf Corporation in Al-Qur'an Tahfizh Learning. The research method used is research and development, the ADDIE model was developed by Reiser and Mollenda. The procedure for making this electronic module includes (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The data analysis technique used in this research is descriptive data analysis technique. The instruments for collecting data in this study were interview guides, observation sheets, validation sheets, practicality sheets. The electronic learning modules that have been developed are then tested for validity by experts using the Aiken V formula and practicality tests by students and teachers. The results showed that the validity of the Tahfizh Al-Qur'an-based learning electronic module obtained a result of 0.83 in the Very Valid category. As for the practicality category, namely the use of Inquiry-based learning electronic modules, it obtained a value of 92.12%. very practical. Based on the results of the validation and practicalization, the Development of E-Modules with Flip Pdf Corporation in Learning Tahfizh Al-Qur'an.